(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, various methods and ways of teaching the French language from elementary grades are considered and studied. There are many advantages of teaching foreign languages in schools from the primary grade. One of the most important factors is that they love the language and arouse their interest in language learning from the day they first step into school.